Therapeutic Efficacy of Liposome-Encapsulated Gentamicin in Rat Klebsiella pneumoniae Pneumonia in Relation to Impaired Host Defense and Low Bacterial Susceptibility to Gentamicin - Schiffelers, Raymond M. (American Society for Microbiology, 2001)
Long-circulating liposomes (LCL) may be used as targeted antimicrobial drug carriers as they localize at sites of infection. As a result, LCL-encapsulated gentamicin (LE-GEN) has demonstrated superior antibacterial activity over the free drug in a single-dose study of immunocompetent rats with Klebsiella pneumoniae pneumonia. In the present study, the therapeutic efficacy of LE-GEN was evaluated by monitoring rat survival and bacterial counts in blood and lung tissue in clinically relevant models, addressing the issue of impaired host defense and low bacterial antibiotic susceptibility. The results show that in immunocompetent rats infected with the high-GEN-susceptibility K. pneumoniae strain, a single dose of LE-GEN is clearly superior to an equivalent dose of free GEN. Yet complete survival can also be obtained with multiple doses of free GEN. In leukopenic rats infected with the high-GEN-susceptible K. pneumoniae strain, free GEN at the maximum tolerated dose (MTD) was needed to obtain survival. However, with the addition of a single dose of LE-GEN to free-GEN treatment, complete survival can be obtained using a sevenfold-lower cumulative amount of GEN than with free-GEN treatment alone. In leukopenic rats infected with low-GEN-susceptible K. pneumoniae cells, free GEN at the MTD did not result in survival. The use of LE-GEN is needed for therapeutic success. Increasing LE-GEN bilayer fluidity resulted in an increased GEN release from the liposomes and hence improved rat survival, thus showing the importance of the liposome lipid composition for therapeutic efficacy. These results warrant further clinical studies of liposomal formulations of aminoglycosides in immunocompromised patients with severe infections.